LITERATURE REVIEW OF PERCEPTION, MATERNAL, PREGNANCY, AND LABOR IN 2015-2021 - Eddy Siswanto; Junardi Harahap (International Journal of Social Science, 2021)
The aim of this literature review was to find out any topics which had discussed and researched scientifically according to behavior, perception, maternal, pregnancy, and labor, especially in 2015 - 2021. The method of literature review was descriptive quantitative. Literatures were tracked by using Mendeley, then selected and processed by using VOS Viewer. They were also manually processed according to completeness of each literature. Of the 4 main discussion clusters had been found, i.e. target clusters, mothers, risk groups, and health services, there were determined several main topics and keywords i.e: examination (care), mothers, factors, experiences, childbirth, and antenatal care. Meanwhile, topics those rarely discussed or researched were perceptions and adolescents. The most collected literatures were published in 2019 (29%), followed by 2020 (22%), and 2015 (15%). Most of the research or studies of the collected literatures were conducted descriptively and took research locations in Indonesia and African countries. Of the selected literatures rose basic assumption that the high maternal mortality rate, especially in Indonesia, is closely related to the lack of utilization of health facilitaties, as a result of the improper behavior of pregnant women in maintaining pregnancy and labor. This behavior is based on mindsets and perceptions related to pregnancy and labor, which have been formed since the pregnant women were teenagers. (9 pt).